Systematic Review of Soft Tissue Sarcomas in Latin America - Marlid Cruz-Ramos; Dorian Yarih García-Ortega; Renata Becerra-Herrera; Denise Carolina Cabello-Díaz; Sara Aileen Cabrera-Nieto; Gabriela A. Martínez-Nava; Claudia Haydeé Saraí Caro-Sanchéz (JCO Global Oncology)
PURPOSESoft tissue sarcomas (STSs) are rare malignant neoplasms posing significant public health challenges globally, especially in Latin America with limited research resources. This systematic review provides an overview of the epidemiology, clinical characteristics, treatment, and outcomes of STSs in Latin America, emphasizing the impact of insufficient investment in research and health care infrastructure.MATERIALS AND METHODSFollowing Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we conducted a systematic literature review of clinicopathologic characteristics of STSs in Latin American patients. Studies published between January 1986 and August 2024 were included. A comprehensive search across multiple databases yielded 502 papers, refined to 18 publications and three national records included in the study. A meta-analysis was done for survival evaluation.RESULTSData from 2,931 patients with mean age 47 years were analyzed, and 340 patients had pretreatment biopsy. The most common sarcoma types were liposarcoma (23.2%) and synovial sarcoma (21.2%), with high-grade tumors (52%) predominating. Treatment primarily involved surgery (863 patients), often combined with radiotherapy (559 patients) and chemotherapy (307 patients). Five-year overall survival was 61%.DISCUSSIONThe findings highlight challenges in managing STSs in Latin America, including advanced disease at diagnosis and high-grade tumors. Survival rates correlate with local advanced disease reported by other countries. Barriers include limited access to specialized centers and inadequate use of preoperative biopsies. Improved diagnostic and treatment strategies and collaborations to enhance research and clinical practices are needed.CONCLUSIONThis review underscores critical gaps in STS management in Latin America. Increased investment in research, a cohesive network of specialized care centers, and a multidisciplinary approach are essential to improve outcomes and quality of life for patients in the region.